218k views
5 votes
Ples help me find slant assemtotes

this one is different because it isn't a rational function



find the slant assemtotes of
(y+1)^2=4xy
the equation can be rewritten using the quadratic formula as
y=2x-1 \pm √(x^2-x)

ples find slant assemtotes and show all work
thx

User Reizo
by
5.5k points

2 Answers

7 votes

which means the other asymptote is the line .

4 votes
A polynomial asymptote is a function
p(x) such that


\displaystyle\lim_(x\to\pm\infty)(f(x)-p(x))=0


(y+1)^2=4xy\implies y(x)=2x-1\pm2√(x^2-x)

Since this equation defines a hyperbola, we expect the asymptotes to be lines of the form
p(x)=ax+b.

Ignore the negative root (we don't need it). If
y=2x-1+2√(x^2-x), then we want to find constants
a,b such that


\displaystyle\lim_(x\to\infty)(2x-1+2√(x^2-x)-ax-b)=0

We have


√(x^2-x)=√(x^2)√(1-\frac1x)

√(x^2-x)=|x|√(1-\frac1x)

√(x^2-x)=x√(1-\frac1x)

since
x\to\infty forces us to have
x>0. And as
x\to\infty, the
\frac1x term is "negligible", so really
√(x^2-x)\approx x. We can then treat the limand like


2x-1+2x-ax-b=(4-a)x-(b+1)

which tells us that we would choose
a=4. You might be tempted to think
b=-1, but that won't be right, and that has to do with how we wrote off the "negligible" term. To find the actual value of
b, we have to solve for it in the following limit.


\displaystyle\lim_(x\to\infty)(2x-1+2√(x^2-x)-4x-b)=0


\displaystyle\lim_(x\to\infty)(√(x^2-x)-x)=\frac{b+1}2

We write


(√(x^2-x)-x)\cdot(√(x^2-x)+x)/(√(x^2-x)+x)=((x^2-x)-x^2)/(√(x^2-x)+x)=-\frac x{x√(1-\frac1x)+x}=-\frac1{√(1-\frac1x)+1}

Now as
x\to\infty, we see this expression approaching
-\frac12, so that


-\frac12=\frac{b+1}2\implies b=-2

So one asymptote of the hyperbola is the line
y=4x-2.

The other asymptote is obtained similarly by examining the limit as
x\to-\infty.


\displaystyle\lim_(x\to-\infty)(2x-1+2√(x^2-x)-ax-b)=0


\displaystyle\lim_(x\to-\infty)(2x-2x√(1-\frac1x)-ax-(b+1))=0

Reduce the "negligible" term to get


\displaystyle\lim_(x\to-\infty)(-ax-(b+1))=0

Now we take
a=0, and again we're careful to not pick
b=-1.


\displaystyle\lim_(x\to-\infty)(2x-1+2√(x^2-x)-b)=0


\displaystyle\lim_(x\to-\infty)(x+√(x^2-x))=\frac{b+1}2


(x+√(x^2-x))\cdot(x-√(x^2-x))/(x-√(x^2-x))=(x^2-(x^2-x))/(x-√(x^2-x))=\frac x{x-(-x)√(1-\frac1x)}=\frac1{1+√(1-\frac1x)}

This time the limit is
\frac12, so


\frac12=\frac{b+1}2\implies b=0

which means the other asymptote is the line
y=0.
User Thierry Falvo
by
5.4k points